Quality Of Life Of Breast Cancer Survivors In Surabaya Breast Cancer Community - Anastasia Putu Martha Anggarani; Raditya Kurniawan Djoar; Riza Amaliya; Fredy Eric Akbar Pamungkas (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: Cancer is a deadly disease for anyone. One type of cancer is breast cancer. This type of cancer has a big psychological impact on sufferers because of the risk of breast removal surgery for sufferers so that cancer can destroy their future and changing quality of life. Decreased quality of life in women with breast cancer causes them to be unable to fulfill their roles, duties and also mantaining health status. Therefore, the purposes of this study are to identified quality of life women with breast cancer. Methods: The method of this study used descriptive analysis, the study was conducted in the breast cancer community in Surabaya, East Java. A total of 30 people became respondents to this study and filled in 30 questions of European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C-30 (EORTC QLQ C30). Results: The general health of the patients was an 664.25, which illustrates that the quality of life for cancer patients is in moderate condition. This is because in this study the last week symptoms such as shortness of breath, weakness, pain, difficulty sleeping, loss of appetite, nausea, vomiting, difficulty defecating, diarrhea, fatigue, difficulty concentrating, tension, difficulty walking close, lying in a chair / mattress is reduced or not. They still find it difficult to do strenuous activities, walk long distances, feel worried, have difficulty remembering and exper.ience financial difficulties. However, their lives are not disrupted due to physicality or therapy Conclusion: The general health of breast cancer patients in the Surabaya breast cancer community is an 664.25, which describes the quality of life of cancer patients in moderate condition . It is expected that the hospital can socialize about the group of breast cancer to patients so that patients can share experience, obtain various health-related information, and will make patients feel they have many friends with cancer fighters so that it will further improve the quality of life